THE INTERNATIONAL CRIMINAL RESPONSIBILITY OF THE FOREIGN FIGHTER - Dr. Salah jubair Saddam (Scholar Express Journals, 2023)
The intensity of international conflicts and wars has increased in many parts of the world, which has led to an increase in the commission of war crimes and violations of international humanitarian law that require punishment. Therefore, the international criminal responsibility borne by agents or representatives of the state, especially members of the armed forces affiliated with the parties to the conflict, and each of the parties to the conflict must bear the responsibility for the violations committed by members of the armed forces affiliated with it according to international humanitarian law. Indeed, a criminal during armed conflicts, he bears responsibility for these acts, and because foreign fighters may commit these criminal acts and their family members, they also bear individual criminal responsibility, and therefore this research was divided into two branches .
Keywords: members; responsibility; individual; foreign